Warrior, king, servant, savior : messianism in the Hebrew Bible and early Jewish texts - Elgvin, Torleif (2022)
"An exegetical and diachronic survey of messianic texts from the Hebrew Bible and Jewish tradition up through the first millennium CE that maintains close dialogue with relevant historical research and archaeological insights"--
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc; Messiah -- Biblical teaching